Human umbilical cord mesenchymal stem cell exosomes alleviate acute kidney injury by inhibiting pyroptosis in rats and NRK-52E cells - Yonghong Wan; Yihang Yu; Chengjun Yu; Jin Luo; Sheng Wen; Lianju Shen; Guanghui Wei; Yi Hua (Renal Failure)
Human umbilical cord mesenchymal stem cells (hucMSCs) have been shown to improve kidney injury. Exosomes have been indicated to be important mediators of renal protection in MSC therapy. In spite of this, the mechanism remains unclear. Our study investigated how exosomes derived from hucMSCs (hucMSC-Ex) improve acute kidney injury (AKI). Exosomes were extracted by using an ultracentrifugation technique and identified by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blot. Twenty-four male SD rats were randomly divided into four groups: sham group, sham + hucMSC-Ex group, ischemia–reperfusion injury (IRI) group, and IRI + hucMSC-Ex group. In vitro, we treated rat proximal renal tubular epithelial cell line (NRK-52E) with cisplatin to mimic in vivo models of AKI. The NRK-52E cells were treated with or without 160 μg/mL hucMSC-Ex, and 1 µg/mL cisplatin was added after 9 h. Cells were harvested after 24 h. In the IRI group, the levels of serum creatinine (Scr) and blood urea nitrogen (BUN) were increased; renal tubules were dilated, epithelial cells were vacuolated, and collagen fibers were deposited in the renal interstitium. After treatment with cisplatin, the NRK-52E cells displayed pyroptotic morphology characterized by pyroptotic bodies. The protein expression levels of fibronectin, α-smooth muscle actin (α-SMA), vimentin, gasdermin D (GSDMD), caspase-1, interleukin-1 (IL-1β) and NLRP3 in IRI tissues and in cisplatin treatment NRK-52E cells were significantly upregulated. However, after the hucMSC-Ex intervention, kidney injury was effectively improved in vivo and in vitro. The current study shows that pyroptosis is involved in AKI and that hucMSC-Ex improves AKI by inhibiting pyroptosis.